PERSEPSI PARTAI POLITIK TERHADAP KETENTUAN KUOTA 30% PEREMPUAN DALAM UU NOMOR 2 TAHUN 2008 TENTANG PARTAI POLITIK (Deskripsi Tentang Persepsi PKB, Golkar, PKS, PPP dan PDIP di Kabupaten Tasikmalaya) - Mohammad Ali Andrias; Wiwi Widiastuti (Fakultas Ilmu Sosial dan Ilmu Politik, 2011)
This research seeks to know the perception of the five political parties (PKB, Golkar, PKS, PPP, and PDI) in the implementing legislation concerning women's representation in political parties and the electoral period 2009-2014, and the constraints faced by women in fulfilling the quota of 30%. With kualitatif.Dapat research methodology concluded that the representation of women in the 2009 legislative election in Tasikmalaya Regency is still very low at only 14% of the normative provisions of 30%. The five parties that became the sampling study, admitted that he had to do the functions of political parties, it's just cultural factors and conventional views of Islam considers women's entrance into the political sphere is something that is taboo. Although the view of Islam in the political sphere think of women as well as lacquers are the same men made no difference in the eyes of God. Representation of women in politics, especially in the legislature should be used as an evaluation, whether the low representation of women in Tasikmalaya Regency is 14% influenced by the electoral system, the internal political party or political and religious culture that has been entrenched in society. Party according to its function should provide a more mature political education to the cadre of women for the women to be better prepared to compete with men - men in the arena of politics, and make more qualified cadre of women in politics so that gender equality can be realized and the representation of women can be fulfilled for the benefit and well being nation.